Porosity–permeability characteristics and mineralization–alteration zones of the Maoping germanium-rich lead–zinc deposit in SW China - Wu, Jianbiao; Han, Runsheng; Zhang, Yan; Wu, Peng; Gong, Hongsheng; Wang, Lei; Cheng, Gong; Li, Xiaodong; Yang, Yixuan; Mi, Yaya (Frontiers in Earth Science, 2024)
The Maoping superlarge germanium-rich lead–zinc deposit is a typical nonmagmatic hydrothermal deposit that is structurally controlled in the Sichuan–Yunnan–Guizhou lead–zinc polymetallic metallogenic area. The orebodies are distributed in several formations. This paper is based on large-scale alteration mapping combined with porosity and permeability measurements. We delineated the mineralization–alteration zones of different ore-bearing formations, explored the geological significance of porosity and permeability, and proposed prospecting directions. The research results indicate that during the mineralization period, the ore-forming metal fluids migrated from the deep part of the SSW region to the shallow part of the NNE region along the ore-guiding structure (Maoping Fault). Through the ore distribution structure, depressurization boiling occurred in the open space of the NE-trending interlayered sinistral compressive–torsional faults in several ore-bearing formations, resulting in fluid precipitation and the formation of different brecciated hot-melt dolomite lead–zinc mineralization zones. From the orebody to the wallrock, the C2w Formation and D3zg Formation are divided into four different mineralization–alteration zones. Tectonic activity affects the properties, migration, and precipitation of fluids, thereby controlling the alteration characteristics generated during fluid migration and thus changing the porosity and permeability. The porosity and permeability of strata on the NW flank of the anticline are greater than those of strata on the SE flank. On the NW flank, the greater the degree of mineralization–alteration is, the greater the porosity and permeability are, and the porosity of the orebody is lower than that during dolomitization. Finally, we believe that the NW flank of the anticline is an important area for prospecting. The pyrite + striped altered dolomite zone (Zones II–III) in the C2w limestone and the pyrite + strong dolomite zone (Zones II–III) in the D3zg dolomite are important prospecting indicators.